Penerapan Media Pembelajaran Kerangka Bangun Ruang untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV di SDN 024761 Binjai Utara - Anggun Agia Arditha; Mona Yuniar Tambunan; Natasya Sihombing; Nanda Septanya Sitanggang; Yohana Gabriella Putri Sitanggang (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The aim of this research is to provide an increase in the Mathematics learning outcomes of class IV students at SDN 024761 North Binjai, and also to find out what form of learning process using spatial framework learning media can increase the learning outcomes of class IV students at SDN 024761 North Binjai. The research was conducted using an experimental approach and involved 15 students as samples. The results of this research prove that efforts to improve mathematics learning outcomes in spatial building materials through experimental activities for class IV students at SDN 024761 North Binjai are at a very good level with a percentage of 95%. The hypothesis that the author proposes in this research is that the application of spatial construction framework learning media can improve mathematics learning outcomes for spatial construction material for class IV students at SDN 024761 North Binjai. And the results of student responses also prove a very satisfactory response to teaching and learning activities using the experimental method.